Artificial intelligence and the rights to assembly and association. Issue 2 (3rd May 2020) - Ashraf, Cameran
ABSTRACT: The rights to assembly and association are fundamental rights guaranteed in the Universal Declaration of Human Rights. They are essential to the establishment and functioning of a democracy and ensure that individuals and groups can peacefully come together to pursue their common goals. These, and other human rights, are being challenged by the development and widespread deployment of artificial intelligence systems on the internet. Indeed, the development of artificial intelligence has been a cause for concern among human rights activists, scholars and practitioners. While much existing literature has examined how AI will impact privacy and freedom of expression, its impact on the rights to assembly and association has been neglected. To develop a more well-rounded body of literature about AI and human rights, this paper will examine the impacts of artificial intelligence on the rights to assembly and association. It will discuss AI's impact on two key areas: content display, whereby AI determines the content we see, and content moderation, where AI determines which content exists . The paper concludes with policy recommendations and the hope that these recommendations will serve as a starting point for a discussion on protecting these important rights in the age of artificial intelligence.